2017
DOI: 10.5152/eurasianjmed.2017.17237
|View full text |Cite
|
Sign up to set email alerts
|

Increased iron deficiency and iron deficiency anemia in children with zinc deficiency

Abstract: Objective: The aim of the present study is to determine the presence of iron (Fe) deficiency and Fe deficiency anemia in children with zinc (Zn) deficiency. Materials and Methods: This retrospective study comprised 560 patients aged 6 months to 16 years in whom Zn levels in hair samples were measured concurrently with serum levels of ferritin, Fe, Fe-binding capacity, and blood count analysis. For all patients, we retrospectively assessed serum ferritin, serum Fe, Febinding capacity, transferrin saturation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Zinc is necessary for iron metabolism, including intestinal absorption and tissue mobilization. The relationship between zinc and hemoglobin reported in human studies [ 23 27 ] supports the use of plasma zinc as a marker for iron deficiency anemia [ 8 ]. However, this relationship has not been developed in patients with eating disorders.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Zinc is necessary for iron metabolism, including intestinal absorption and tissue mobilization. The relationship between zinc and hemoglobin reported in human studies [ 23 27 ] supports the use of plasma zinc as a marker for iron deficiency anemia [ 8 ]. However, this relationship has not been developed in patients with eating disorders.…”
Section: Discussionmentioning
confidence: 66%
“…In females, iron stores can be depleted among patients who are menstruating [ 21 ]. Animal studies have demonstrated that zinc is required for iron metabolism [ 22 ] and numerous human studies have established the correlation between low zinc and low hemoglobin [ 23 27 ]. Zinc could, therefore, plausibly be used as a marker of iron deficiency anemia.…”
Section: Introductionmentioning
confidence: 99%
“…It functions as a cofactor or structural stabilizer for more than 300 enzymes throughout the body and directs a wide array of biochemical and cellular processes, including signal transduction, ribonucleic acid (RNA) transcription, and cellular growth, division, and differentiation [5][6]. Interestingly, patients with IDA have been shown to have significantly reduced serum levels of zinc while IDA is significantly more prevalent in patients known to have zinc deficiency [7][8][9]. More specifically, zinc deficiency has been speculated to contribute to the development of IDA through the inhibition of the intestinal absorption of iron as well as its mobilization from tissue stores [10].…”
Section: Discussionmentioning
confidence: 99%
“…The zinc-deficient diet increased plasma hepcidin level, consistent with reduced intestinal iron absorption ( 109 ). There might be a physiological crosstalk between iron and zinc in erythropoiesis because clinical studies revealed that patients with iron deficiency anemia were significantly associated with zinc deficiency ( 110 , 111 ). Moreover, zinc supplementation stimulates erythropoiesis while zinc plus iron more efficiently ameliorated anemia than iron alone ( 112 , 113 ).…”
Section: Prevention Of Iron-induced Liver Damage By Nutrientsmentioning
confidence: 99%